Folliculin interacts with p0071 (plakophilin-4) and deficiency is associated with disordered RhoA signalling, epithelial polarization and cytokinesis - Nahorski, Michael S.; Seabra, Laurence; Straatman-Iwanowska, Ania; Wingenfeld, Aileen; Reiman, Anne; Lu, Xiaohong; Klomp, Jeff A.; Teh, Bin T.; Hatzfeld, Mechthild; Gissen, Paul; Maher, Eamonn R. (Human molecular genetics, 2012)
Inherited mutations in the folliculin (FLCN) gene cause the Birt-Hogg-Dubé syndrome of familial hair follicle tumours (fibrofolliculomas), lung cysts and kidney tumours. Though folliculin has features of a tumour suppressor, the precise function of the FLCN gene product is not well characterized. We identified plakophilin-4 (p0071) as a potential novel folliculin interacting protein by yeast two-hybrid analysis. We confirmed the interaction of folliculin with p0071 by co-immunoprecipitation studies and, in view of previous studies linking p0071 to the regulation of rho-signalling, cytokinesis and intercellular junction formation, we investigated the effect of cell folliculin status on p0071-related functions. Folliculin and p0071 partially co-localized at cell junctions and in mitotic cells, at the midbody during cytokinesis. Previously, p0071 has been reported to regulate RhoA signalling during cytokinesis and we found that folliculin deficiency was associated with increased expression and activity of RhoA and evidence of disordered cytokinesis. Treatment of folliculin-deficient cells with a downstream inhibitor of RhoA signalling (the ROCK inhibitor Y-27632) reversed the increased cell migration phenotype observed in folliculin-deficient cells. Deficiency of folliculin and of p0071 resulted in tight junction defects and mislocalization of E-cadherin in mouse inner medullary collecting duct-3 renal tubular cells. These findings suggest that aspects of folliculin tumour suppressor function are linked to interaction with p0071 and the regulation of RhoA signalling.